Comparison of application rate of three commercial litter amendment products on litter pH, ammonia volatilization, and broiler paw scores during the brooding period - M. Grimes; E. Jiral; A. LeBlanc; J. Rocha; G.S. Archer (Journal of Applied Poultry Research, 2025)
Summary: The objective of this study was to evaluate the duration of effectiveness of 3 commercially available litter acidifying amendments during the brooding period when chicks were housed at either half- or whole-house stocking densities. The treatments included control pens with no litter amendment product applied, PLT® (Poultry Litter Treatment, Jones-Hamilton Co.) and Poultry Guard® (PG; C&S Chemicals) at 0.49, 0.61, and 0.73 kg/m2, and Al+Clear® A7 (A7; Chem Trade Logistics) at 0.81, 1.02, 1.22 L/m2. In Experiment 1, broiler chicks were housed at 0.08 m2/bd (whole-house density) and at 0.04 m2/bd in Experiment 2 (half-house density). Both experiments utilized used litter from a commercial broiler farm placed into 5 pens per treatment in an experimental poultry facility. In Experiment 1, broiler chicks were reared in the pens for 15 d while chicks were reared to d 10 in Experiment 2. Data collected included litter parameters of moisture and pH, ammonia flux and bird performance. In both experiments, the application of PLT and PG resulted in lower litter pH than A7. All treatments also reduced litter ammonia flux compared to control (P < 0.05) in both experiments. In both experiments, PLT maintained a lower ammonia release compared to the other treatments through the end of each experiment. No differences (P > 0.05) in litter moisture, BW or FCR were observed between treatments in either experiment. PLT and PG at the highest application rate did improve average paw quality scores at d 15 in Experiment 1. These data demonstrate that at both stocking densities the 3 litter amendment products evaluated were able to reduce litter pH and ammonia flux compared to control.